Olfactory and imaging features in atypical Alzheimer’s disease - Huihong Zhang; Pan Wang; Chunfeng Zhang; Yan Wang; Hui Zhang; Li Cai; Yuying Zhou (Translational Neuroscience, 2018)
Cognition and speech disorders are the most common symptoms of dementia in neurodegenerative disease. Here, we present a detailed clinical evaluation of a case of logopenic variant of primary progressive aphasia (lv-PPA), an atypical form of Alzheimer disease (AD), including cognitive testing over time, brain imaging, electrophysiology, and tests of olfactory function.